SUPER PREMIUM DESTINATION! : PERAN TOURIST EXPECTATION TERHADAP INTENSI BERKUNJUNG KE LABUAN BAJO - Akhrani, Lusy Asa; Cahyaningsih, Firda Ayu (Psychopreneur Journal, 2024)
This study aims to determine the role of tourist expectations on the intention to visit Labuan Bajo. This study involved 500 tourists who are Indonesian citizens over 17 years of age and have the intention to visit the super-premium tourism of Labuan Bajo and were obtained using a purposive sampling technique. The scale used Tourist Expectation scale and Theory of Planned Behavior (TPB) scale. Data analysis in this study was carried out using simple regression data analysis techniques which resulted in an 8.1% role for tourists' expectations of super premium tourism in Labuan Bajo by 8.1% on the intention to visit the super-premium tourism of Labuan Bajo. It has a positive significance relationship, that is if tourist expectations on the super-premium tourism of Labuan Bajo increase, the intention to visit tourists will also increase.